The Role of School Administrative Staff in the Quality of School Services - Umnia, Jauharotul; Wiyono, Bambang Budi; Timan, Agus (Proceedings Series of Educational Studies, 2024)
School administrative staff are resources responsible for managing educational administration. Without the presence of administrative staff, the management of education cannot be carried out perfectly. However, in reality, administrative activities, especially in supporting the achievement of the school's vision and mission, have not yet received balanced treatment. Even at the elementary school level and in special education, the activities are not handled by specialized staff but are instead taken on by the principal or the existing teachers. The purpose of the researcher conducting the study on the role of school administration in improving the quality of school services is to understand the management of administration carried out to enhance the quality of school services. This research uses a qualitative literature study method. The result of the research indicates that the role of school administrative staff is crucial in carrying out administrative functions in schools. Therefore, several aspects that need to be considered in the management of school administrative staff include: proper placement of positions, training and development of administrative staff competencies, supervision, and performance evaluation of administrative staff.